Influence of reputation on shareholder value - Runge Christopher (SHS Web of Conferences, 2021)
Research background: This paper focuses on the topic of reputation management. Reputation is a social construct. It is based on a person’s opinion of another person, thing, or organization. It is also highly dependent on group interactions and the socio-cultural environment. A good reputation is equated with a high standing and the attributes credibility, honesty, reliability, responsibility, and trust play a major role here. This also applies to companies. The literature offers numerous studies in which the influence of reputation on brand value or company value is examined. Their common tenor is that they lead to the conclusion that essentially a relationship exists between reputation, brand value, and shareholder value. Purpose of the article: The aim of this paper is to empirically test how reputation can influence shareholder value. As a proxy variable, reputation is represented by the change in the brand value of companies. Methods In this study, data from the EIKON database of Thomson Reuters and data for brand values from Interbrand were used. For a total of 147 companies, the share prices, sales revenues, EBITDA, and the market-to-book ratio were recorded on the basis of the ISIN. In addition, brand values were summarized for these companies according to Interbrand. It should be noted that the figures varied from year to year, as data was also missing or newly added during the years. Thus, depending on the study, a smaller number than 147 companies were analyzed. Data from 2010 to 2020 were collected and analyzed. In the univariate regression analysis performed, we first tested whether the change in reputation could explain the change in company performance. Subsequently, further regression analyses were conducted to test whether the reputation can explain profit margin and market-to-book ratio. Findings & Value added: The results show the influence of reputation on selected variables.